EEG study on implicit beliefs regarding sexuality: Psychophysiological measures in relation to self-report measures - van der Linde, Robin; van Boxtel, Geert; Masthoff, Erik; Bogaerts, Stefan (Frontiers in Psychology, 2022)
In this exploratory, correlational study, several psychophysiological measures were assessed and the relation between these measures and a self-report questionnaire to measure the seven implicit beliefs of sexual offenders (the QITSO) was established in a sample of Dutch participants recruited from the healthy population (N = 28) using correlational analyses. After analyzing task performance, electroencephalogram (EEG) data and electrocardiogram (ECG) data, the psychophysiological variables were correlated with the QITSO subscales. The subscale ‘children as sexual beings’ correlated positively with the P300 amplitude at electrode Pz. The subscale ‘women are unknowable’ correlated positively with resting-state beta activity during eyes closed and eyes open, and with alpha activity during eyes open. Additionally, the subscale ‘entitlement’ correlated positively with low frequency heart rate variability power during eyes closed and eyes open, and with high frequency power during eyes closed. This study is a first exploratory step towards establishing a psychophysiological profile underlying the self-report questionnaire QITSO.